Mussolini and the eclipse of Italian fascism : from dictatorship to populism - Bosworth, R. J. B. (New Haven : Yale University Press, 2021)
On the tenth anniversary of his rise to power in 1932, Benito Mussolini (1883-1945) seemed to many the "good dictator." He was the first totalitarian and the first fascist in modern Europe. But a year later Hitler's entrance onto the political stage signaled a German takeover of the fascist ideology.0 In this definitive account, eminent historian R.J.B. Bosworth charts Mussolini's leadership in reaction to Hitler. Bosworth shows how Italy's decline in ideological pre-eminence, as well as in military and diplomatic power, led Mussolini to pursue a more populist approach: angry and bellicose words at home, violent aggression abroad, and a more extreme emphasis on charisma. In his embittered efforts to bolster an increasingly hollow and ruthless regime, it was Mussolini, rather than Hitler, who offered the model for all subsequent authoritarians
Frontmatter -- Contents -- Plates -- Abbreviations -- Introduction -- 1. Mussolini and the ghost of Adolf Hitler -- 2. The peculiarities of Italian history and the many birthdays of 1932-3 -- 3. A thriving dictatorship: Fascist, totalitarian or Mussolinian? -- 4. Imagining liberal totalitarianism? -- 5. An Italian dictatorship, its dreams of empire and the enveloping shadow of Nazism -- 6. Populist totalitarianism and/or Fascist mysticism under the Duce -- 7. The Fascist map of Europe moves to Africa: Ethiopia, empire and their consequences -- 8. An Axis of evil, Fascist racism and a waning dictator 1936-40 -- Conclusion. Worst of dictators? The meaning of Benito Mussolini and Italian Fascism in the age of Trump and the populists -- Notes -- Further reading -- Acknowledgements -- Index
Includes bibliographical references and index.
Online resouce; title from PDF title page (JSTOR, viewed April 22, 2021).
JSTOR
Keywords: Mussolini, Benito, -- 1883-1945.; Mussolini, Benito, -- 1883-1945; Fascism -- Italy; Italy -- Politics and government -- 1922-1945.; Fascisme -- Italie; Italie -- Politique et gouvernement -- 1922-1945.; HISTORY -- Europe -- Italy; HISTORY -- Modern -- 20th Century; Fascism; Politics and government; Italy; 1922-1945